Effect of brassinolide on certain enzymes of sorghum grown in saline soils of Karaikal - Vidya Vardhini, B (Journal of Phytology, 2012)
The effect of brassinolide on the activities of certain enzymes like IAA oxidase, protease and ribonuclease of two sorghum varieties (‘CSH-5’ and ‘CSH-6’) grown in four saline experimental sites of Karaikal viz. Varchikudy, Pogalam, Kilavur and Mallavur, was studied. Brassinolide-treatment resulted in lowered IAA oxidase, protease and ribonuclease activities. The study revealed that brassinolide was more effective in lowering the enzyme activities in Mallavur than other saline sites (Pogalam, Kilavur and Varchikudy).